ADMINISTRATION-TIME-DEPENDENT EFFECTS OF CANAGLIFLOZIN IN TYPE 2 DIABETIC PATIENTS AND ARTERIAL HYPERTENSION. (June 2018) - Ameijeiras, A. Hermida; Fernandez-Crespo, S.; Paz, J.E. Lopez; Rodriguez, I.; Gomez, C. Calvo
Abstract : Objective: Nocturnal hypertension is more frequent in diabetics, due to the dysfunction of the autonomic nervous system. Several prospective studies have concluded that nocturnal BP is a better predictor of CV mortality than daytime BP or even, than the 24-hour average. Renal inhibition of the sodium-glucose co-transporter type 2 (SGLT2) leads to an increase in urinary sodium excretion and, therefore, to a relative depletion of volume that results in a drop in blood pressure. No reported data have evaluated the efficacy of SGLT2 inhibitors in terms of nighttime blood pressure reduction regarding the time-based administration of the treatment. Figure. No caption available. Design and method: Phase IV, unicentric, prospective, randomized and open study of parallel groups evaluated in the Hypertension and Vascular Risk Unit of the University Clinical Hospital of Santiago de Compostela with diagnosis of Diabetes Mellitus type 2 (DM2). 36 patients were randomized to the two treatment arms (canagliflozin 100 mg before breakfast Vs canagliflozin 100 mg before dinner) and were followed up for 24 weeks. The systolic, diastolic and heart rate of each patient were monitored every 20 minutes during the daytime period (07:00 am to 11:00 pm) and every 30 minutes during the night period for at least 24 consecutive hours, using a device oscillometric SpaceLabs 90207® (SpaceLabs Inc., Redmon, Washington). Results: Greater decrease of nocturnal systolic blood pressure was observed when canagliflozin was administered at bedtime. Similar results were observed when analyzing the nocturnal decrease in diastolic blood pressure. Conclusions: Our data showed a decrease on nocturnal BP in hypertensive patients with DM type 2, after the administration of canagliflozin 100 mgrs at bedtime. This antihypertensive effect is not objectified when the administration was at daytime. Due to high prevalence of nocturnal arterial hypertension in patients with DM type 2, the results provided might support the use of ABPM and the administration of SGLT-2 co-receptor inhibitors according to a chronotherapy regimen.